Synchronous biological feedbacks in parrotfishes associated with pantropical coral bleaching. (2nd December 2019) - Taylor, Brett M.; Benkwitt, Cassandra E.; Choat, Howard; Clements, Kendall D.; Graham, Nicholas A. J.; Meekan, Mark G.
Abstract: Biological feedbacks generated through patterns of disturbance are vital for sustaining ecosystem states. Recent ocean warming and thermal anomalies have caused pantropical episodes of coral bleaching, which has led to widespread coral mortality and a range of subsequent effects on coral reef communities. Although the response of many reef‐associated fishes to major disturbance events on coral reefs is negative (e.g., reduced abundance and condition), parrotfishes show strong feedbacks after disturbance to living reef structure manifesting as increases in abundance. However, the mechanisms underlying this response are poorly understood. Using biochronological reconstructions of annual otolith (ear stone) growth from two ocean basins, we tested whether parrotfish growth was enhanced following bleaching‐related coral mortality, thus providing an organismal mechanism for demographic changes in populations. Both major feeding guilds of parrotfishes (scrapers and excavators) exhibited enhanced growth of individuals after bleaching that was decoupled from expected thermal performance, a pattern that was not evident in other reef fish taxa from the same environment. These results provide evidence for a more nuanced ecological feedback system—one where disturbance plays a key role in mediating parrotfish–benthos interactions. By influencing the biology of assemblages, disturbance can thereby stimulate change in parrotfish grazing intensity and ultimately reef geomorphology over time. This feedback cycle operated historically at within‐reef scales; however, our results demonstrate that the scale, magnitude, and severity of recent thermal events are entraining the biological responses of disparate communities to respond in synchrony. This may fundamentally alter feedbacks in the relationships between parrotfishes and reef systems. Abstract : By reconstructing growth histories of coral reef fishes, we demonstrate that parrotfishes exhibit a growth benefit following coral bleaching disturbance. This benefit scales from the individual to population and assemblages levels and reflects a nutritional subsidy conferred through microbial succession. Overall, we found synchronized assemblage‐level responses between ocean basins, reflecting a troubling signal of the magnitude and scale of contemporary climate change impacts.